Isolation and identification of Wickerhamiella tropicalis from blood culture by MALDI-MS - Takei, Satomi; Teramoto, Kanae; Fujimura, Junya; Fujiwara, Megumi; Suzuki, Mai; Fukui, Yukiko; Sekiguchi, Yuji; Kawakami, Takaaki; Chonan, Masayoshi; Wakita, Mitsuru; Horiuchi, Yuki; Miida, Takashi; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Wickerhamiella is a genus of budding yeast that is mainly isolated from environmental samples, and 40 species have been detected. The yeast isolated from human clinical samples usually only contain three species: W. infanticola, W. pararugosa and W. sorbophila. In this study, we isolated W. tropicalis from a blood sample of a six-year-old female with a history of B-cell precursor lymphoblastic leukemia in Japan in 2022. Though the strain was morphologically identified as Candida species by routine microbiological examinations, it was subsequently identified as W. tropicalis by sequencing the internal transcribed spacer (ITS) of ribosomal DNA (rDNA). The isolate had amino acid substitutions in ERG11 and FKS1 associated with azole and echinocandin resistance, respectively, in Candida species and showed intermediate-resistant to fluconazole and micafungin. The patient was successfully treated with micafungin. Furthermore, matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) detected three novel peaks that are specific for W. tropicalis, indicating that MALDI-MS analysis is useful for rapid detection of Wickerhamiella species in routine microbiological examinations.